Theoretical Predictions for the Equation of State of Metal Nickel at Extreme Conditions - Sihan Wu; Yueyue Tian; Boyuan Ning; Huifen Zhang; Xijing Ning (Metals, 2025)
A recently developed approach to the partition function with very high efficiency was applied to study the equation of state (EOS) of metal nickel (Ni) up to 3000 K and concurrently 500 GPa. The theoretical results agree very well with previous hydrostatic experiments at room temperature, and at high temperatures, the deviation of our calculated pressures from the latest hydrostatic experiments up to 109 GPa is less than 4.16%, 4.95%, and 5.53% at 1000, 2000, and 3000 K, respectively. Furthermore, an analytical EOS model with only two parameters was developed for common metals at high temperatures, and the analytical EOS of metal Ni was obtained to produce the map of pressure over the temperature–volume plane, which should be helpful to understand the thermodynamic properties of Ni-based alloys.